Topology Optimization of Static Turbomachinery Components - Buonamici, Francesco; Meli, Enrico; Secciani, Nicola; Ridolfi, Alessandro; Rindi, Andrea; Furferi, Rocco (Manufacturing Technology Journal, 2023)
Additive Manufacturing has enabled the design of complex components in several technical fields. Considering turbomachinery components, additive manufacturing has unlocked the achievement of significant performances for dynamic rotoring components. The application of topology optimization methods is one of the main factors accelerating the technological development of this sector. This paper presents a procedure for the optimization of static turbomachinery components. The frame-work proposed compares the results obtained by introducing a lattice structure and a solid optimized shape. The procedure is presented with reference to a specific case study. To validate the proposed framework, the complete re-design of a thrust collar of a major Italian-based Oil&Gas company is carried out, demonstrating that the re-thinking of the component in terms of Topology Optimization is a straightforward approach to increase the overall performance of the produced part.
Keywords: Topology optimization; turbomachinery; thrust washer; dynamic optimization